A new species of the genus Rapturella (Gastropoda: Acteonidae) from southeast Brazil - Cunha, Carlo M.; Simone, Luiz Ricardo L. (Zootaxa, 2018)
Acteonidae d'Orbigny, 1843 is the largest family within the superfamily Acteonoidea (Bouchet et al. 2017) and includes small gastropods typical of infralittoral environments. Most acteonids living on the continental shelf or in deep water have been described on the basis of shell morphology alone (Simone 2006; Valdés 2008; Cunha 2011; Salvador & Cunha 2016), because little material with soft parts has been collected and examined. Consequently, little is known about the ecology of the species.  Recently, many new species of the genus Acteon Montfort, 1810 have been described from tropical Southwest Pacific waters (Valdés 2008), suggesting that a high diversity of acteonid species may await discovery in other deep water environments, including those of Brazil.